Environmental Factor Relationship To Coral Growth of Goniopora stokesi in Waters of Laelae Island And Barranglompo Island - Dedy Kurniawan; Jamaluddin Jompa; Abdul Haris (Riau University, 2020)
Goniopora stokesi coral is one of the massive corals on Laelae Island and Barranglompo Island. Massive coral growth in the formation of coral skeleton sedimentation rate (CaCO3) is highly dependent on the environment. The research objective was to analyze the differences in the growth rates of G. stokesi, as well as the relationship between environmental factors and the growth rates of G. stokesi corals in Laelae Island and Barranglompo Island. This study uses secondary data on coral growth of G. stokesi and data on environmental conditions from 2009 to 2013, in the waters of Laelae Island and Barranglompo Island. Differences in coral growth rates were analyzed using One Way ANOVA analysis, if there were significant differences followed by a significant difference test according to the Bonferroni method, with SPSS 19.00 software. Analysis of the relationship between environmental factors and coral growth using the Principle Component Analysis (PCA) test with Microsoft Excel 2003 software. The results showed that the environmental conditions in the waters of Laelae Island and Barranglompo Island showed a range of values that were not too different, only the traffic, current, and turbidity values were different between the two islands. The coral growth rate of G. stokesi on Laelae Island was 9.72 ± 1.16 mm year-1, while on Barranglompo Island it was 12.47 ± 2.67 mm year-1. The coral growth of G. stokesi on Laelae Island was affected by high currents and turbidity, while on Barranglompo Island it was influenced by high salinity.